A DECADE OF SOFTWARE REUSE: A RESEARCH DIRECTION - Fatin Izatul Nadia Mohd Zulkurnain, Suryani Ismail, Masita Masila Abdul Jalil, Fatihah Mohd (International Journal of Advanced Science and Technology, 2020)
Software reuse has been one of the most interesting research topics for more than forty years ago. Throughout that time, the interest shown in this area is growing rapidly and contributed to many results being published. There is a broad knowledge and experiences enclosed in conferences and journals focusing on this field. Hence, there are a number of issues that need to be further addressed. The major focus of this study is to investigate the current trends in software reuse research through a detailed literature review. A detailed literature review study is done based on various sources such as Web of Science (WoS), SCOPUS, ScienceDirect, IEEE Xplore and ACM Digital Library (ACM DL) which has been selected from January 2009 until December 2019. Using the available resources, this study highlights two aspects of software reuse which are the intensity of research activity and the research topics. The mentioned trends indicate that software reuse is still one of the interesting fields that call for further research.